Oxygen consumption and blood lactic acid response to training and taper - van Handel, P. J.; Katz, A.; Troup, J. P.; Daniels, J. T.; Bradley, P. W. (Swimming Science V, 1988)
Detraining or taper is commonly practiced in preparation for competition, but it may result in significant reductions in aerobic capacity and endurance in running (Hickson, Foster, Pollock, Galassi, & Rich, 1985) and muscle force and power in swimming (Neufer, Costill, Fielding, Flynn, & Kirwan, 1986). The purpose of this study was to monitor energetics during intense training and taper in highly trained swimmers in preparation for U.S. national competitions.